Deciphering decadal observation of Fukushima-derived radiocesium in the most polluted port near the Fukushima Daiichi Nuclear Power Plant: from seawater to marine fish - Lin, Wuhui; Zhang, Yibang; Du, Jinqiu; Xuan, Jiliang; Tuo, Fei (Frontiers in Marine Science, 2024)
The biological concentration effect of radionuclides in marine fish has exacerbated public anxiety about seafood security in the context of Fukushima nuclear-contaminated water discharged into the ocean. However, the most polluted port near the Fukushima Daiichi Nuclear Power Plant (FDNPP) has seldom been investigated, especially for radioactivity in marine fish. In this study, decadal observations of radiocesium in marine fish and seawater from the most polluted port were simultaneously established after the Fukushima Nuclear Accident. We found a generally decreasing trend of historical 137Cs activity in seawater, with seasonal variations modulated by precipitation. Seasonal variations were elucidated with finer detail and divided into exponential decline in the dry season and steady variation in the wet season. A novel method was proposed to estimate the continuing source term of 137Cs derived from the FDNPP, which was 3.9 PBq in 2011 and 19.3 TBq between 2012 and 2022 on the basis of historical 137Cs. The biological concentration effect of marine fish is quantitatively emphasized according to the higher ratio of over-standards for radiocesium in marine fish relative to that in seawater. Long-term observation and analysis of radiocesium in marine fish and seawater from the most polluted port would provide insights into the scientific evaluation of the effectiveness of the decommissioning of the FDNPP in the past and share lessons on the fate of Fukushima-derived radionuclides in the future.